The role of the arts on community mental health and cultural understanding in Addis Ababa, Ethiopia - Hearst, Mary O.; Belay, Melaku; Wilcox, Hui (Frontiers in Public Health, 2023)
Background In low-and middle-income countries, there are rising rates of depression and anxiety. In Ethiopia, depression and anxiety rates were rising before the COVID-19 pandemic, and the country faces ethnic discord and armed conflict. Novel community-based strategies are needed to improve mental health and cultural unity. The purpose of this research was to describe the role of a cultural center’s art programming in mental health and cultural unity. Methods This qualitative study conducted interviews and focus groups with audience members, artists, and staff at Fendika Cultural Center, Addis Ababa, in January 2023. Participants were recruited via word of mouth and purposive sampling. Focus groups and interviews led in English or Amharic were recorded, transcribed, and translated as needed. Questions included participant experiences with Fendika Cultural Center and how experiencing the arts at Fendika influences wellbeing. We used deductive analysis, guided by the Arts and Culture in Public Health Framework. Results Two focus groups (n = 11 participants, five females and six males) and five key informant interviews (three females and two males) were completed. Findings suggested that the activities at Fendika were important for addressing individual depression and anxiety through the social and physical environments as well as the inherent cultural support and unity expressed through the arts. The themes were consistent with the Arts and Culture in Public Health Framework. Conclusion The arts play an important role in positive mental health and cultural unity. Further research is needed to establish the generalizability, reach, and persistence of the impact of cultural centers on mental health cultural understanding.